The Level of Environmental Knowledge of Phase C Elementary School Students Regarding Waste Management - Ridha, Mhd; Fannisa, Hani; Zain, Bella Putri; Zulkarnain, Aissy Putri (Postgraduate School, Universitas Negeri Padang, 2025)
Waste issues represent an increasingly complex environmental challenge that requires behavior change through education from an early age. Environmental education at the elementary school level plays a crucial role in developing environmental literacy and sustainable waste management behavior. This study aims to describe the level of environmental knowledge of Phase C elementary school students (Grades V and VI) regarding waste management. A descriptive quantitative approach was employed involving 150 students. The instrument consisted of a 15-item multiple-choice test covering fundamental waste concepts, organic and inorganic classification, environmental impacts, the 3R principles (reduce, reuse, recycle), waste sorting, and environmental care attitudes. Data were analyzed using descriptive statistics, including mean, median, mode, and percentage distribution. The findings indicate a mean score of 12.23 (high category), with 70% of students categorized as high and 30% as moderate, and none in the low category. Correct response rates were very high for conceptual and normative indicators but relatively lower for applicative aspects such as the implementation of 3R principles and waste sorting. These findings suggest that while foundational knowledge is well established, practice-based and systematic habituation strategies remain necessary to transform knowledge into practical waste management skills within the school environment.